1997
DOI: 10.1080/004982597240334
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the calcium antagonist, mibefradil (POSICOR™, Ro 40-5967). Part II. Metabolism in hepatic microsomes from rat, marmoset, cynomolgus monkey, rabbit and man

Abstract: 1. The calcium antagonist, mibefradil, is converted to some 30 metabolites after incubation with hepatic microsomes from the rat, marmoset, cynomolgus monkey, rabbit and man.2. The wide inter-species diåerences in metabolic pro®le stem mainly from variations in the activity of the microsomal esterase, which hydrolyses the ester side-chain of mibefradil to give the alcohol metabolite, Ro 40-5966. Hydrolysis is especially marked in the cynomolgus monkey and rabbit, less in man and least in the rat and marmoset.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Metabolism consists of a combination of P450-mediated oxidation, hydrolysis of the ester side chain by CYP3A4 and esterases, and conjugation with glucuronic acid by UDP glucuronosyltransferases (UGTs) (Wiltshire et al, 1997b;Ernst and Kelly, 1998). One of the major hydrolyzed metabolites, Ro 40-5966 ( Fig.…”
mentioning
confidence: 99%
“…Metabolism consists of a combination of P450-mediated oxidation, hydrolysis of the ester side chain by CYP3A4 and esterases, and conjugation with glucuronic acid by UDP glucuronosyltransferases (UGTs) (Wiltshire et al, 1997b;Ernst and Kelly, 1998). One of the major hydrolyzed metabolites, Ro 40-5966 ( Fig.…”
mentioning
confidence: 99%
“…This study reported that the AUC (area under the curve) of mibefradil in plasma for the final dose given on day 8 was 7797 ± 1323 ng h/mL [6], equivalent to~11-16 μM. Mibefradil is efficiently processed by cytochrome P450-catalysed hydrolysis and its metabolites typically represent 50-80% of the circulating drugrelated compounds after a single oral dose of 100 mg [5]. Considering that our in vitro studies showed a LogEC 50 around 45-50 μM for mibefradil and that micromolar (≥ 10 μM) concentrations significantly raised [Ca 2+ ] cyt (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Mibefradil, a T-type voltage-gated calcium (Ca 2+ ) channels (Ca v 3.1-3.3) inhibitor, was launched by Roche as Posicor® for the treatment of hypertension and stable angina at doses containing 50-100 mg once a day [1,4]. The maximum plasma circulating levels of mibefradil were around 1 μg/mL after 1-2 h of the single 100 mg dose [4,5]. Although mibefradil has a potent effect on T-type CCA, being 10to 30-fold higher for T-type than L-type [4], adverse clinical outcomes resulted in its withdrawal from the market in 1998 because of drug-drug interactions, sideeffects, and inhibition of cytochrome P450 3A4 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon that plasma concentrations of mibefradil rose more than the dosage ratio had been observed in humans previously (Welker et al, 1998). According to a report on the metabolic pathway of mibefradil, oxidative metabolites were major (Wiltshire et al, 1997b). Therefore, this nonlinear pharmacokinetics seemed to occur as a result of the autoinactivation of metabolism of mibefradil by MBI.…”
Section: Discussionmentioning
confidence: 99%